Size-dependent electromagnetic properties and the related simulations of Fe3O4 nanoparticles made by microwave-assisted thermal decomposition - Liang, Yi-Jun; Fan, Fengguo; Ma, Ming; Sun, Jianfei; Chen, Jun; Zhang, Yu; Gu, Ning (Colloids and surfaces. A, Physicochemical and engineering aspects, 2017)
To insightfully understand the size-dependent electromagnetic properties of magnetic NPs will be of great importance to explore their microwave applications. [Display omitted] •High performance Fe3O4 NPs with different sizes were ultra-fast prepared by microwave assisted thermal decomposition approach.•The size-dependent electromagnetic properties of these Fe3O4 NPs were studied systematically.•The micromagnetic simulation (OOMMF) was used to insightfully understand the size effect associated with energy variation in electromagnetic filed. A great deal of effort has demonstrated magnetite nanoparticles (Fe3O4 NPs) are important subject applied in tumor hyperthermia due to their excellent magneto-thermal effect. Our previous study had ultrafast prepared 6nm Fe3O4 NPs via microwave approach and found that these small size NPs are responsible for microwave energy conversion to accelerate NPs formation. Hence, we suppose that investigating the size-dependent behavior of Fe3O4 NPs should be beneficial for developing their electromagnetic energy conversion application for hyperthermia. In this study, Fe3O4 NPs with four sizes (i.e. 4nm, 20nm, 50nm and 200nm) were prepared by a rapid microwave synthetic strategy. The specific absorption rate (SAR) value and reflection loss (RL) value of samples were investigated by measuring the time-dependent temperature curves in alternating magnetic field (AMF, 390 and 780kHz, 12A) and via vector network analyzer (VNA) range from 2 to 18GHz, respectively. Results indicated that using magnetic induction hyperthermia frequency Fe3O4 NPs with single domain size of 20nm possess maximum, whereas the RL value increases with the size at microwave frequency. More importantly, the frequency of maximum RL value was matched with the clinical microwave hyperthermia. We subsequently introduce the micromagnetic (OOMMF) simulation to help understanding the issue due to the fundamental importance of size effect for magnetic NPs in energy conversion. Simulation results suggested that coupling interaction and magnetic dipole-dipole interaction between magnetic NPs and electromagnetic field would be seen as synergistic effect to impact absorption behavior, and we believe that this work can provide a valuable reference for size selection of magnetic nanoparticles in clinical application of hyperthermia.